Papalele and Market: Traditional Exchange in Saparua Island, Maluku - Junianita Fridianova Sopamena; August Ernst Pattiselanno (JSW (Jurnal Sosiologi Walisongo), 2021)
The island market has become the culture of the small-island community that was formed due to limited transportation facilities, the market only exists at certain times. Markets develop from the process of exchanging goods between people coming from different places and profession. This study aims to describe the process of commodity marketing, the role of papalele in the exchange of farmers' and fishermen's products, and the commodity market formed in society. This research uses a case study approach because of a typical island market that only exists on small islands such as Saparua Island. The informants consisted of fifteen papalele mothers spread over fifteen regions in the island (negeri) and always carried out activities to the island market in Saparua City. The research results showed that the marketing process for agricultural commodities begins with an exchange between farmers and fishermen. Then it developed with various exchange processes with the presence of papalele women. Commodities eventually developed with the movement of papalele as a collector at the region level, and later became recipients of pawns for agricultural commodities, even collecting agricultural and fishery commodities from the region around where they lived. Finally, a permanent market was formed in Saparua Island, on Wednesday and Saturday._________The original draft of this article has been presented on the 6th International Conference on Social and Political Sciences (ICoSaPS) 2020, Strengthening Resilient Society in The Disruptive Era, Surakarta, October 7-8th, 2020.